Performance of Lactating Cows Fed with Dried Poultry Manure in a Corn Silage Based Complete Ration - Rustamadji, Bugi (Faculty of the Graduate School University of the Philliphines at Los Banos, 1983)
Twelve pregnant Holstein x Red Sindhi cows were used in a randomized complete block design experiment to evaluate protein supplementary value of dried poultry manure (DPM) in corn silage based complete rations for early lactation. There levels of DPM in concentrate mixtures were 0,30 and 50 percent. Dry matter intake and body weight changes were not significantly different among the three rations. Actual milk production , projected 350-day lactation and persistency of milk production among groups of cows were not significantly different. Likewise, no significant differenceswere found in milk fat, total solids, solids-not-flavor, oferall acceptance and off-flavor of milk. However, 4 percent fat corrected-milk yield and income over feed cost were found to be significantly (P/.05) better with 30 percent DPM in the concentrate. With DPM making up 12 pecent of the dry matter, complete TDN were found favourable for early lactating cows under the humid tropical conditions of Los Banos, Philippines.